Kinerja Ekonomi Sektor Logistik di Provinsi Maluku Utara - Muhammad Zais M. Samiun; Nurdin I. Muhammad (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to examine the economic performance of the logistics sector, especially in the formation of gross regional domestic product. Based on secondary data, the data was analyzed using descriptive method, sector contribution index and sector growth index. The analysis found that the logistics sector is one of the most important in the economy. The performance of the logistics sector is closely related to the dynamics of each economic sector and the economy in aggregate. The logistics sector in the formation of GRDP comes from the transportation and warehousing sector. In reflecting economic performance, the transportation sector plays the biggest role in shaping the performance of the logistics sector. In the case of North Maluku, land transportation is the best performer. Meanwhile, sea transportation and air transportation are still underperforming and are easily shocked when global and domestic economic conditions are under pressure.